A CROSS-SECTIONAL STUDY ABOUT FACTORS ASSOCIATED WITH TEENAGE PREGNANCY AMONG TEENAGE GIRLS AT KAYUNGA HOSPITAL KAYUNGA DISTRICT. - Namutebi, Phionah; Otieno, Joash Odiwuor; dyamuhaki, Denis (Student’s Journal of Health Research Africa, 2024)
Background The purpose of the study was to determine the factors associated with teenage pregnancy among teenage girls at Kayunga Hospital Kayunga district. Specific objectives were to determine the knowledge of teenage girls toward teenage pregnancy and the socio-economic factors associated with teenage pregnancy among teenage girls. Methods A descriptive cross-sectional study was conducted among 100 teenagers in Kayunga Hospital Kayunga district. Data were collected using a structured questionnaire, entered, and analyzed appropriately. Results The majority of the respondent 69(69%) had not heard of teenage pregnancy whereas 31(31%) had heard. Most of the respondents 10(33.3%) sourced information about teenage pregnancy from school whereas 5(16.7%) from parents. The majority of the respondents 68(68%) stated that the father of the child is an elderly man whereas 32(32%) stated young man is the father. Peer pressure was the most cited reason for indulgence in sexual activities 45(45%), and culture accounted for 8(8%). Conclusion The results have presented a lack of knowledge among the teenagers as the majority have not heard of teenage pregnancy. The socio-economic factor predisposed most of the respondents to sexual activities. Recommendation Community sensitization, comprehensive sexuality education, and ensuring girls enroll and stay in schools could reduce adolescent pregnancy rates. Also, the provision of adolescent-friendly health services in schools and healthcare centers and the initiation of adolescent empowerment programs could have a positive impact.